The market segmentation workbook : target marketing for marketing managers - Dibb, Sally, 1963-; Simkin, Lyndon (London ; New York : Routledge, 1995)
This book is about: The market segmentation process; Core analyses; Strategy; Programmes for implementation; ...
Keywords: Marketing; Segmentation; Market segmentation